(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to identify the efficiency and the adequacy of government policies in combating money laundering crime to point out the level of coordination between the relevant authorities in combating the crime of money laundering, to monitor the challenges facing the fight against the crime of money laundering, and to highlight the experiences of other countries in combating this crime. The importance of the study lies in answering the main question: to what extent do government policies contribute to combating money laundering crime in the State of Palestine? The importance of the study also appears in the seriousness of the crime of money laundering; it is estimated that it has reached 6% of the Palestinian GDP. To achieve the goals of the study, it followed the descriptive analytical approach by running a survey that involved conducting 9 interviews with relevant and specialized persons in the field of combating money laundering. In addition to using the purposeful sampling technique by distributing 54 questionnaires to employees in the specialized institutions, in addition to using the content analysis method. The researchers reached several results, the most important of which were that the effectiveness of government policies affects the fight against the crime to a high degree, at a rate of 81 percent and that the government policies specialized in combating the crime are sufficient to a high degree, at a rate of 78 percent. In addition, there is coordination to a moderate degree, at a rate of 67.7%, between the relevant authorities in combating the crime of money laundering. The most prominent recommendations were the need to expedite the publication of reports related to the crime of money laundering in all its details.